PENGARUH STRUKTUR KEPEMILIKAN PERUSAHAAN TERHADAP TINDAKAN PAJAK AGRESIF - Listyo Cahyo Purnomo (Badan Pendidikan dan Pelatihan Keuangan - Kementerian Keuangan Republik Indonesia, 2016)
Based on APBNP-2015 , tax contributes about 70 percent of states revenue. In the other side, Tax is a significant cost of business. Based on this, many companies are trying to reduce the cost of the tax though tax planning. This study aims to determine the effect of coorporate ownership and tax aggresiveness, based on sample of LQ45 firms in IDX from 2010 to 2014. This study use Effective tax rate (ETR) as measurement of tax aggresiveness. The result of this study : (1) a negative significant relationship between tax aggresiveness and family ownership ;(2) a positive significant relationship between tax aggresiveness and government ownership; (3) and no significant relationship in foreign ownership. Negative sign of ETR indicates that the family ownership are more aggresiveness in tax planning.